2020
DOI: 10.1177/2382120520912744
|View full text |Cite
|
Sign up to set email alerts
|

Training in Interventional Radiology: A Simulation-Based Approach

Abstract: Innovations in medical technology have revolutionised both medical and surgical practice. Indeed, with such innovations, training for specific specialties has become more advanced and streamlined. However, despite these novel approaches to train students and specialist trainees, training for interventional radiology (IR) is lagging. While the reason for this lag remains contentious, one of the primary reasons for this issue may be the lack of standardisation for IR training due to a scarcity of specific guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…20e24 A simulation-based curriculum 25 could supplement practical skills training and maintenance of existing procedural skills. Multiple studies have shown that there is a role of simulation training in both the acquisition of endovascular skills for new learners, as well as learning for more experienced operators 26 ; however, it is not able to completely replace procedural training in real cases. In addition to simulation, a survey among ophthalmology trainees 24 showed that webbased real-time case presentations for clinical training and discussion of edited surgical videos for procedural training are the most desired training supplementation, with potential to be adapted for IR training.…”
Section: Discussionmentioning
confidence: 99%
“…20e24 A simulation-based curriculum 25 could supplement practical skills training and maintenance of existing procedural skills. Multiple studies have shown that there is a role of simulation training in both the acquisition of endovascular skills for new learners, as well as learning for more experienced operators 26 ; however, it is not able to completely replace procedural training in real cases. In addition to simulation, a survey among ophthalmology trainees 24 showed that webbased real-time case presentations for clinical training and discussion of edited surgical videos for procedural training are the most desired training supplementation, with potential to be adapted for IR training.…”
Section: Discussionmentioning
confidence: 99%
“…25 Simulation-based technology and immersive training environment for IR have also been proposed. 74,75 A complementary business model of medical subspeciality training that incorporates the private sector has been developed for reproductive medicine in South Africa by Dalmeyer et al 76,77 The authors are convinced that the model can be applied to other subspecialities.…”
Section: Recommendationsmentioning
confidence: 99%
“…They offer standardized training scenarios, improving procedural skills i.e. vascular trauma management, uterine and prostatic artery embolization [4,20]. Those simulators are reusable, provide feedback, measure procedure and uoroscopy times.…”
Section: Discussionmentioning
confidence: 99%